Quality of medical education in Mexico - Alonso-Caballero, Álvaro; Mériγo-Azpiri, Carlos Alberto (My University, 2004)
Sir—Rafael Santana-Davila and Cristina Martinez (Jan 24, p 329)1 address some issues about medical education in Mexico. We would like to clarify some information to avoid general misconceptions. Currently Mexico has 78 medical schools, not 56, an average of 2·4 per state. Mexico’s physician to population ratio is about 1:600, similar to that of Great Britain or Germany.2 However, the distribution of physicians is unequal because most specialists live in main urban areas, leaving most rural areas unattended.